(untitled) (Journal of Plant Disease Sciences, 2021)
Bacterial blight disease of pomegranate caused by Xanthomonas axonopodis pv. punicae is one of the most destructive disease inflicting considerable quantitative and qualitative losses. Cultural and biochemical variability of eight isolates of X. axonopodis pv. punicae (Xap), collected from diverse agro- climatic zone consisting eight district of Maharashtra, India were studied. Out of the nine isolates tested their cultural and biochemical variations, most of them showed variability in colour, size, shape, elevation and appearance on NA media. Xap-2 had found highly pathogenic as shown more lesion size i.e. 0.9 mm after 15 days and 3.4 mm after 21 days of inoculation however, Xap-5 showed lowest lesion size 0.2mm after 15 days and 1.5 mm after 21 days of inoculation. The studies on biochemical characteristics of X. axonopodis pv. punicae showed their positive reactions for gelatine liquification, catalase test, potassium hydroxide (KOH) solubility test, H2S Production, tolerance to 1% NaCl, and starch hydrolysis whereas, negative response for Gram staining, indole production and methyl red test. Isolates Xap-2, Xap-3, Xap-4, Xap-5 grew moderate at pH 6.0 and other isolates Xap-1, Xap-6, Xap-7 and Xap-8 showed less growth at pH 6.0. It is considered that distinct variability existed among the X. axonopodis pv. punicae isolates collected from different locations/Districts of the Maharashtra.